Лингвистическое новаторство виленских изданий скорины - Аниченко, В. В.; Паруков, А. А. (Kalbotyra, 1986)
The article is devoted to the language of Skorina’s texts of the “Pslater” (the Prague’s and Vilna’s editions). The authors indicate that the influence of the national Byelorussian language is noticeable in the language of these texts.